Acordo União Europeia-Turquia (2016) frente à crise humanitaria dos refugiados sirios : avanços, consolidações ou retrocessos ? - Victor Albuquerque Felix da Silva; Tomaz Espósito Neto (Confins)
This article seeks to answer the following question: to what extent does the European Union-Turkey Agreement (2016) comply with the Convention Relating to the Status of Refugees and the Protocol Relating to the Status of Refugees? The general objective of this investigation is to analyze the European Union-Turkey Agreement, and the specific objectives are to analyze the emergence, evolution and consolidation of international regimes for refugees; to address the political, economic and social context of the Syrian Arab Republic; and to discuss the provisions made by the European Union-Turkey Agreement. This is a qualitative research, which questions the European Union-Turkey Agreement on the violation of the international regime for refugees. The method used here was the case study method combined with document analysis of primary and secondary sources made available by the European Union, Republic of Turkey, NGOs and UN agencies, as well as a selected review of the literature on international regimes and the refuge institute.